2014
DOI: 10.1002/etc.2534
|View full text |Cite
|
Sign up to set email alerts
|

Partial least square and k‐nearest neighbor algorithms for improved 3D quantitative spectral data–activity relationship consensus modeling of acute toxicity

Abstract: A diverse set of 154 chemicals that included US Food and Drug Administration-regulated compounds tested for their aquatic toxicity in Daphnia magna were modeled by a 3-dimensional quantitative spectral data-activity relationship (3D-QSDAR). Two distinct algorithms, partial least squares (PLS) and Tanimoto similarity-based k-nearest neighbors (KNN), were used to process bin occupancy descriptor matrices obtained after tessellation of the 3D-QSDAR space into regularly sized bins. The performance of models utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…In the last 2 years our group has been using this rather stringent 20 %-Hold-Out and 100 random partitions validation process as standard procedure for quality assurance [ 1 , 3 , 4 , 22 ]. This standard has recently been evaluated by others and confirmed as both necessary and appropriate for estimating QSAR model predictive accuracy of external data [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the last 2 years our group has been using this rather stringent 20 %-Hold-Out and 100 random partitions validation process as standard procedure for quality assurance [ 1 , 3 , 4 , 22 ]. This standard has recently been evaluated by others and confirmed as both necessary and appropriate for estimating QSAR model predictive accuracy of external data [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…We built and modeled 2D > 3D conformations for 130 estrogens and 154 acute toxicity compounds previously modeled by 3D-QSDAR [ 1 , 4 ]. Predictive accuracy, R Test 2 , was compared for these endpoints to estimate the circumstances under which one might effectively take advantage of the 2D > 3D shortcut and save 93–97 % of modeling time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assumption is that the strengths of one model will counterbalance the weaknesses of the others and vice versa. Previous studies have already shown the beneficial effects of consensus modelling when dealing with ecotoxicological endpoints [39][40][41][42].…”
Section: Consensus Modellingmentioning
confidence: 96%